The role of artificial intelligence in ensuring the efficiency and accessibility of justice - Кирилюк, Алла Володимирівна; Кирилюк, А. В.; Kyryliuk, Alla V.; Крикун, Вячеслав Віталійович; Крикун, В. В.; Krykun, Viacheslav V.; Щокін, Ростислав Георгійович; Щокін, Р. Г.; Shchokin, Rostyslav H.; Галупова, Лариса Ігорівна; Галупова, Л. І.; Halupova, Larysa I.; et al. (Belo Horizonte : Editora Fórum LTDA, 2024)
Information technologies are changing our world extremely fast. The availability of information technologies opens new opportunities but presents challenges. The above contributes to the relevance of applying artificial intelligence (AI) in the justice system. E-justice should facilitate digital market development, which is an essential e-government task. The legal industry has always been known for relying on tradition and resisting change. However, recent advances in AI technology are nimble to disrupt the legal landscape, changing how law firms and legal departments work. The article aims to clarify how to use AI to improve the efficiency and speed of judicial processes and analyze examples of successful implementation of AI systems in the legal field. The article determines the advantages and disadvantages of AI used in justice and examines the issue of accessibility and justice in the context of AI in justice. This research is relevant since it offers an in-depth understanding and analysis of new technologies in the context of legal challenges. It is possible to resort to this research when developing effective strategies for implementing artificial intelligence in the legal field, which constitutes its practical implication.
Krykun V. The role of artificial intelligence in ensuring the efficiency and accessibility of justice / V. Krykun, R. Shchokin, A. Kyryliuk et al. // Revista Brasileira de Alternative Dispute Resolution. – Belo Horizonte : Editora Fórum LTDA, 2024. – 6(12). – P. 267–289. Режим доступу: https://hdl.handle.net/11300/32348
Keywords: Artificial intelligence; Electronic justice; Computer Technologies; Judiciary; International practice; National legislation